Productive performance of Brangus cattle at weaning in grazing conditions in Colombia - Motta-Delgado, Pablo Andrés; Benítez-Vásquez, Carolina; López-Perea, Maira Alejandra; Plaza-Cárdenas, Johanna Alessandra; Dussan-González, Camilo; Peñaloza-Galeano, Milton Emiliano (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The aim of this study was to evaluate and compare the performance of Brangus calves at weaning under grazing conditions, and determine the influence of the sex on its performance. This study was conducted in the Cartago municipality (Colombia), in a herd dedicated to the production of beef with Brangus breed. The data were analyzed by ANOVA with a 95% significance using the statistical software InfoStat 2015. Full records of second lactation cows that were served by the same bull were evaluated to reduce the error factor. The variables evaluated were: weight at birth, weight at weaning, meat production index and average daily gain (ADG). The following model of age at weaning was considered as a covariate: Yij=u+Ti+BXij+Eij. The weight at birth was 33.22±1.86 and 31.88±0.89 kg for males and females respectively, weight at weaning was 246.00±51.69 and 225.81±21.78 kg respectively, rate of production was 0.64±0.12 and 0.62±0.05% respectively, ADG was 890±280, 850±100 grams/day respectively, and age at weaning of 251.78±44.01 and 228.19±16.30 days respectively. Only statistical significant difference for weight at birth (p=0.0286) was observed. In conclusion, both males and females Brangus showed differences in birth weight, however, differences in meat production levels are not significant since these reach at weaning similar weight, meat production index and average weight gain. In this sense, the productive trend may be similar at post-weaning stage, being feasible to employ both males and females interchangeably for the production of beef, additionally, the heifers can arrive faster at age for bull service.